Zooplankton Seasonal Abundance in Relation to Physico-Chemical Features in Mahapoli Lake, Bhiwandi, Maharashtra (Global Journal of Science Frontier Research, 2017)
Physico-chemical analysis and zooplankton survey of the Mahapoli Lake was carried out on monthly basis for the period of one year from February-2016 to January-2017. PH determined alkaline nature of the lake ranging 7.2 to 7.9, Dissolved oxygen 4.2-7.77mg/l was recorded. Alkalinity (97 to 183mg/l), total Hardness (69 to 142 mg/l), chlorides (45 to 63 mg/l) and the nutrients like phosphates and nitrates were at maximum in summer and minimum in rainy season. During the study period, total 10 species of zooplankton were identified by three groups such as Rotifera (4sp), copepoda (3sp) and cladocera (3sp).The highest numbers of zooplanktons were recorded in summer months and lowest in rainy season.
Keywords: physico-chemical; zooplankton; rotifera; cladocera; copepoda; mahapoli village